CuWO4 as a novel Z-scheme partner to construct TiO2 based stable and efficient heterojunction for photocatalytic hydrogen generation. (8th December 2022) - Bharagav, U.; Reddy, N. Ramesh; Rao, V. Navakoteswara; Ravi, P.; Sathish, M.; Shankar, M.V.; Kumari, M. Mamatha
Abstract: Synthesis of highly efficient, stable, visible active CuWO4 nanoparticles through a simple methodology, paves a feasible path for enhancing the efficiency of TiO2 . A novel nanocomposite of CuWO4 NP loaded TiO2 NR heterojunction was mounted through a direct Z-scheme mechanism. Optimized composite CWT-3, advances the photocatalytic hydrogen production rates of TiO2 to 106.7 mmol h −1  g −1 cat . CuWO4 incorporation as OEP compensates inefficiency of WO3 and other Z-scheme combinations reported so far, on limiting the charge carrier recombination followed by the generation of a greater number of excitons. Specific amounts of catalyst loading, study on the effect of sacrificial reagents, and understanding the effect of the light source, are the three pivotal steps that helped here to hamper the density of overall back reactions. The formation of Z-scheme heterojunction was evidently confirmed on determining the position of CBM and VBM, PL and photoelectrochemical analysis. Recyclability studies further proved the stable and efficient outcomes of CWT-3 for five consecutive cycles. Based on photocatalytic activity, employing BDF by-product glycerol as an optimized sacrificial reagent serves the oxidation demands and triggered 53.26% solar to hydrogen conversion efficiency under natural sunlight irradiation. Highlights: A noble metal-free combination of TiO2 nanorods-CuWO4 nanoparticles binary composite was reported for the first time. The OEP role CuWO4 was explored through Z-scheme heterojunction for enhanced exciton separation. H2 production activity of optimized photocatalyst CWT-3 was evaluated using glycerol as hole scavenger under controlled experiments. HER and OER matching band positions facilitate efficient H2 rates of about 106.7 mmol h −1  g −1 cat . Recyclability studies evidently claim that CWT-3 was stable and efficient for H2 generation under solar light irradiation.